Saint Anselm of Canterbury and Charismatic Authority - Aird, William M. (Religions, 2014)
The early career of Archbishop Anselm of Canterbury (c. 1033-1109) provides an opportunity to explore the operation of charismatic authority in a monastic setting. It is argued that the choice of Anselm for the archiepiscopal see of Canterbury in 1093 was the result of his growing reputation cultivated during his years as prior and abbot of the influential Norman monastery of Bec. The article explores various aspects of Anselm’s charismatic authority including his performance of charisma, the charisma derived from his fame as a scholar, and his reputation as a miracle-working holy man.